Translating Two Minds in the Tradition of One Faith: Considerations of Intercultural Dynamics in the parallels of John Henry Newman (1801-1890) and Joseph Ma Xiangbo (1840-1939) - Law, Cyril Jerome (Sacred and the Everyday: Comparative Approaches to Literature, Religious and Secular, 2021)
Interculturality is considered a constant given in the development of most major religious movements during the process of propagation coming into contact with diverse tongues, mores, and sentiments. And one of the chief, if not decisive, instruments contributing to this ever dynamic spread and reception of beliefs and cultures is translation. Christianity purports to be an incarnational religion, where the Word made flesh expresses the di-vine in human terms. Its doctrines are enshrined in a faith tradition that is developed largely through interpretation and translation. This short paper will cut into this sacral literary tradition by paralleling two influential mod-ern Christian thinkers, John Henry Newman from the Anglophone school, and Joseph Ma Xiangbo from the Orient, to see how attempts at translating the ideas and works of people from distinct cultural milieux is both reflec-tive of the necessary developmental nature of Christian teachings in the historical continuum of time and space, and indicative of the intellectual challenges that never cease to accompany the literary effervescence stem-ming from comparative religious studies.

「道」與「導」：與聖紐曼樞機反思生命中皈依與教學之使命 Leading the Way - Reflecting on the Mission of Learning and Conversion of Life with St John Henry Newman (1801-1890) - Law, Cyril Jerome (2021)